2020
DOI: 10.1177/0886260520961870
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Forensic Evidence: Examining Sexual Assault Medical Forensic Exam Mechanisms that Influence Sexual Assault Case Outcomes

Abstract: Despite the widespread use of sexual assault medical forensic exams (SAMFEs), practitioners and researchers continue to debate the role of SAMFEs and the evidence they provide in the investigation and prosecution of sexual assault cases. Using data from a review of sexual assault cases reported to police between 2015 and 2017 in two jurisdictions ( n = 534), we use logistic regression examine whether the presence of a SAMFE predicts the likelihood of achieving criminal case processing outcomes and whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Lack of injuries may also deter survivors from coming to hospitals for care because they may not think it is serious enough for urgent care, 33 yet the hospital is often the only place where forensic evidence is collected for further legal action. 34 The increasing risk of violence and sexual assault was anticipated from the beginning of the pandemic in association with financial loss, fear of COVID-19 infection, and social isolation, including being isolated with a potentially controlling and abusive person. A comprehensive response to reducing violence and sexual assault during COVID-19 involves reducing harms among survivors, including improved access to victim services (eg, referrals, accompaniment services, safety planning, and mental health support), clinical care, and social support for leaving dangerous and violent environments.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 99%
“…Lack of injuries may also deter survivors from coming to hospitals for care because they may not think it is serious enough for urgent care, 33 yet the hospital is often the only place where forensic evidence is collected for further legal action. 34 The increasing risk of violence and sexual assault was anticipated from the beginning of the pandemic in association with financial loss, fear of COVID-19 infection, and social isolation, including being isolated with a potentially controlling and abusive person. A comprehensive response to reducing violence and sexual assault during COVID-19 involves reducing harms among survivors, including improved access to victim services (eg, referrals, accompaniment services, safety planning, and mental health support), clinical care, and social support for leaving dangerous and violent environments.…”
Section: Jama Network Open | Emergency Medicinementioning
confidence: 99%
“…One study found that while forensic evidence was predictive of arrest and charging of sexual assault suspects, it was not predictive of conviction (Johnson et al, 2012). Others have found that forensic evidence was not significantly related to arrests of suspects (Schroeder & Elink-Schuurman-Laura, 2017;Tiry et al, 2020). This also can be seen through studies that document how police often make arrests before DNA evidence is submitted for examination or results are returned: in one study, less than half of DNA testing was complete before an arrest was made (Schroeder & Elink-Schuurman-Laura, 2017).…”
Section: Samfes Impact On Sexual Assault Case Outcomesmentioning
confidence: 99%
“…5See Tiry et al (2020) for findings from the sexual assault case file reviews, including key case processing details.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both crimes concerning sexual and domestic violence were analysed, considering the possible contribution that a detailed medical examination can give in such cases. A preliminary specific analysis on victims examined in a specialized centre was made, in order to improve medico-legal care quality; as previously stated, indeed, physicians who take part in these cases often have no feedback on the legal consequences of their intervention [16] and in recent years few studies worldwide have addressed medico-legal findings and epidemiological data impact on legal outcome [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%